Un nouveau fragment de moule à sigillée du Centre-Ouest à Marcilly-sur-Vienne (Indre-et-Loire) - Thomas Boucher; Richard Delage; Alain Ferdière (Revue Archéologique du Centre de la France)
A fragment of a mold for sigillata was discovered in 2004 in Marcilly-sur-Vienne, near the Gallo-Roman agglomeration, with workshops of potters, of Nouâtre (Indre-et-Loire). It corresponds to sigillata productions of the group called Centre-Ouest, probably from the beginning of the second century. Stylistic comparisons are shown with the sigillata productions of the center of Gaul, and in particular of Martres-de-Veyre.